The Inhibitory Action of Dantrolen Sodium on Agonist-Induced Contractions in Isolated Rat Myometrium - Ayar, Ahmet; Tuğ, Niyazi (Fırat University, 2001)
The aim of this study was to investigate the actions of the anti-malignant hyperthermia drug dantrolene-sodium on contractions of myometrium isolated from rat. Myometrium strips were obtained from rats after killing by servical dislocation and suspented in a double-jacketed organ bath containing Krebs solution at 37°C, continuously gassed with %5 CO2+%95 O2. After development of spontaneous contractions under one gram resting tension oxytocin (65 mU/L) prostaglandin F2α (1 µM), KCl (20 mM) or dantrolene-sodium (10-30µM) was applied. The effects of these agents on mean peak amplitude and frequency of contractions were evaluated by 10 minute periods, pantrolene sodium significantly inhibited the peak amplitude of oxytocin and prostaglandin F2&alpha-induced (p0.05)contractions in a dose dependent manner. In conclusion, dantrolene-sodium inhibits contractions induced by oxytocin and prostaglandin F2α possible by inhibiting Ca+2 release from intracellular stores.

Bu çalışmanın amacı anti malign hipertermik ilaç dantrolen sodyumun izole sıçan miyometriyumunda kasılmalar üzerine olan etkilerini incelemektir. Sıçanlar servikal dislokasyonla öldürüldükten sonra miyometriyum şeritleri alınarak içerisinde 37°C'de Krebs solüsyonu bulunan ve %5 CO2+ %95 O2 ile sürekli gazlandırılan çift çeperli organ banyosunda asıldı. Bir gramlık istirahat gerimi altında spontan kontraksiyonlar geliştikten sonra oksitosin (65 mU/L) prostaglandin F2α (1 µM), KCl (20 mM) ve dantrolen sodyum (10-30µM) uygulandı. Bu ajanların konfeksiyonların ortalama pik amplitüt ve frekans değerleri üzerine etkileri 10 dakikalık periyotlar halinde incelendi. Dantrolen sodyum oksitosin ve prostaglandin F2α ile indüklenen kontraksiyonların pik amplitütlerini doza bağımlı olarak inhibe etti (p0.05). Sonuç olarak dantrolen sodyum oksitosin ve prostaglandin F2α ile indüklenen kasılmaları muhtemelen hücre içi depolardan kalsiyum salıverilmesini bloklayarak inhibe etmektedir.
DANTROLEN SODYUMUN İZOLE SIÇAN MİYOMETRİYUMUNDA AGONİSTLERLE İNDÜKLENEN KASILMALARA İNHİBİTÖR ETKİSİ